The Singapore sting : the key to corporate governance in Singapore - Ang, Tracy Pei Fang (2008)
Singapore is known for having a good corporate governance regime. We aim to find the key factor that contributed to the reputation. We have found that criminal sanctions is the key to corporate governance in Singapore.